2018
DOI: 10.1016/j.arth.2017.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty in Patients With Parkinson Disease: Improved Outcomes With Dual Mobility Implants and Cementless Fixation

Abstract: Our study shows that elective primary or revision THA using cementless implants with dual mobility bearing surface in patients with PD provides satisfactory long-term outcomes, although many of these patients may see a general worsening of their activities over time due to PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…There has been a trend toward the use of dual mobility implants in high-risk dislocation populations such as PD patients; these have recently shown good longterm results. 26 The type of approach and implant used could not be determined given the database data and is a limitation that could have prevented discerning a significant difference in dislocation risk in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There has been a trend toward the use of dual mobility implants in high-risk dislocation populations such as PD patients; these have recently shown good longterm results. 26 The type of approach and implant used could not be determined given the database data and is a limitation that could have prevented discerning a significant difference in dislocation risk in our study.…”
Section: Discussionmentioning
confidence: 96%
“…6 However, the present study's sample size exceeds or is comparable with previous studies evaluating the impact of comorbid PD on various outcomes following primary THA. 22,26,28,29 In addition to stratification by disease stage, prospective studies investigating the effects of cup style and individual comorbidities such as diabetes mellitus or obesity would improve the strength of analysis, as accounting for these unobserved covariates would alleviate the limitations, and resulting potential bias, imposed by propensity-score matching. 30,31 This, along with a larger sample size, would increase the generalisability of our findings to the Parkinson's disease population as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have demonstrated that THA and TKA are safe in patients with Parkinson's disease and achieve excellent pain control [16][17][18][19]. Functional outcomes are less clear, but longer term are likely related at least in part to disease progression [13,14,39].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on THA and TKA outcomes in PD patients is largely limited to case series of operations performed between the 1970s and 1990s [11][12][13][14][15]. Of the larger studies that have been done, all demonstrated that PD patients experienced relief of pain, the most common reason for surgery, but changes in functional status were less consistent [16][17][18][19]. Studies of perioperative complications associated with TKA and THA have suggested that comorbid PD is associated with increased rates of perioperative urinary tract infection, cognitive dysfunction, blood transfusion, periprosthetic infection, hip fracture, or dislocation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Auch in einer retrospektiven Analyse von 59 Parkinsonpatienten, die mit einer zementfreien Hüftendoprothese mit DMC versorgt wurden, zeigte sich nach durchschnittlich 8,3 Jahren keine Dislokation. Jedoch traten eine IPD sowie vermutlich sturzbedingt 4 periprothetische Frakturen auf [60]. In 2 Untersuchungen an gemischten Kollektiven von Hochrisikopatienten (neurodegenerative Erkrankungen, Alter über 70 bzw.…”
Section: Neuromuskuläre Erkrankungenunclassified